Introduction Of Good Manufacturing Practices (GMP) And Mechanical Equipment To Improve Production Process Of SME Rotterdam Bakery - Wahyunanto Agung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT Improvement and quality control in food processing is to be done in order to improve the competitiveness of the food product. Purpose of service activities is to introduce the implementation of Good Manufacturing Practice (GMP) to Rotterdam Bakery SMEs to achieve high competitiveness in the market. To support this, three pieces of mechanical equipment is introduced, the automatic oven, proofer anti rust and wet dough mixer horizontal type. The result of the introduction of science and technology shows an increase in the production of bread almost doubled from SMEs Rotterdma bakery than prior to introduction. From kenambelas points GMPimplementation, until now still new Rotterdam can carry four points perfectly. Keywords: GMP, food, SME